Phylogenetic analysis of Yunnan flowering cheery cultivar Cerasus ‘Hongxia’ based on chloroplast genome - Chengmin YAN; Wei ZHENG; Xiaodan XU (Guangxi Zhiwu, 2023)
Cerasus ‘Hongxia’, a Yunnan flowering cheery cultivar blooming in March with semi-double to double pink petals, have been widely cultivated in central Yunnan for its high ornamental value. It was regarded as the cultivar of Cerasus cerasoides var. rubea. However, it was clustered in C. campanulata based on molecular markers. Therefore, the phylogeny of these cultivars are doubtful, which is not conducive to their breeding and cultivation. In order to explore the origin of Cerasus ‘Hongxia’, with leaf DNA of Cerasus ‘Hongxia’ as material, chloropast genome characteristics were sequenced by Illumina, assembled, annotated, and analyzed by bioinformatic methods, and analyzed by MISA and Genious R10. The phylogenetic tree of Cerasus was reconstructed by using RAxML 8.0, and the phylogenetic relationship of Cerasus ‘Hongxia’ was analyzed. The results were as follows: (1) The chloroplast genome of Cerasus ‘Hongxia’ was 157 832 bp in length, containing a pair of reverse repeat sequence (inverted repeat sequence，IR, 26 381 bp) regions, which were separated by a short single copy (SSC, 19 120 bp) region and a long single copy (LSC, 85 950 bp) region. A total of 128 genes were encoded, including 84 protein-coding genes, 36 tRNA genes and 8 rRNA ribosomal genes. The overall Guanine and Cytosine content of genome was 36.73%. (2) Based on the maximum likelihood phylogenetic tree analysis of 16 chloroplast genome of Cerasus, it was found that Cerasus ‘Hongxia’ was formed as sister to C. subhirtella and C. yedoensis, and was far away from C. cerasoides. Therefore, we speculated that Cerasus ‘Hongxia’ may be a hybrid cultivar of C. campanulata and C. subhirtella or C. yedoensis, rather than the cultivar of C. cerasoides. The above results are be useful for studies of the origination and genetic breeding of Cerasus ‘Hongxia’, as well as the cultivar identification and classification of C. cerasoides.